Serum magnesium status among obese children and adolescents - Ali M. Zaakouk; Mohammed A. Hassan; Omar A. Tolba (SpringerOpen, 2016)
Background and objectives: Serum magnesium is involved in the pathogenesis of obesity and its related diseases. The aim of the present study was to evaluate serum magnesium status in obese children and adolescents and to study its relationship with the degree of obesity and serum lipid profile. Design and settings: A cross-sectional study was conducted at the general pediatric out-patient clinic of a university hospital, over a period of 5 months from May to September 2013. Methods: 50 obese subjects of ages 2-16 years and 50 healthy normal weight subjects of matched age and sex as controls were consecutively enrolled. Comprehensive history, anthropometric measurements and blood pressure were taken. BMI and degree of obesity were calculated. Fasting total serum magnesium, total cholesterol, LDL-cholesterol, HDL-cholesterol and triglycerides were measured. Results: Obese cases compared to normal weight controls showed significantly lower serum magnesium and HDL-cholesterol levels and significantly higher total cholesterol, LDL-cholesterol, triglycerides, systolic and diastolic blood pressures. Serum magnesium showed a significant, strong inverse correlation with the degree of obesity (r = −0.8, p < 0.001); significant, moderate inverse correlation with total cholesterol and LDL-cholesterol; and non-significant correlation with triglycerides and HDL-cholesterol. The degree of obesity showed a significant, moderate positive correlation with total cholesterol and LDL-cholesterol and a non-significant correlation with triglycerides and HDL-cholesterol. Conclusion: Serum magnesium levels are inversely correlated with the degree of obesity, and is related to an unfavorable serum lipid profile in obese children and adolescents, who also show a trend to higher systemic blood pressure.